The Economic Effects of a Russia-EU FTA - Miriam Manchin (Tinbergen Institute, 2004)
The paper examines the effects of Russia joining the WTO taking into accountenergy sector reform and the impact of a future Free Trade Agreement (FTA) between theenlarged EU and Russia. The paper uses Computable General Equilibrium Modellingtechniques for quantifying the different possible scenarios. The scenarios include astandard assessment of the removal of tariff barriers including agriculture, services andremoval of non-tariffbarriers. The results suggest that a potential FTA would be beneficialfor Russia only if it would incorporate not only reduction in industrial tariffs but also inagriculture and liberalisation in services.
Keywords: F13; F15; 330; EU-Russia Free Trade Agreement; WTO accession; trade liberalization; CGE modeling; Freihandelszone; Russland; EU-Staaten; WTO-Mitgliedschaft